Norovirus occurrence and tissue localization in farmed Mediterranean mussels (Mytilus galloprovincialis) from Sardinia, Italy - M. Molotzu; A. Canu; T. Tedde; S. Virgilio; R. Bazzardi; R. Sau; S. Salza; G. Piras; S. Cau; B. Soro; J.G. Pereira; J.C.F. Pantoja; et al. (Food Research International, 2026)

DNA metabarcoding for the identification and relative abundance assessment of general and potentially pathogenic bacteria in Sardinian sheep cheese processing environments - L. Giagnoni; S. Salza; A. Tondello; G. Zardinoni; Deb. Saptarathi; G. Piras; R. Melillo; A. Cecchinato; P. Stevanato; T. Tedde; A.G. Mudadu; A. Squartini; et al. (International Journal of Food Microbiology, 2025)

Application of droplet digital PCR for the detection of fish DNA in food products - S. Cau; B. Soro; R. Melillo; G. Piras; S. Salza; T. Tedde; F. Pinna; B. Vodret; C. Spanu (Food Research International, 2025)

Association between rainfall and Escherichia coli in live bivalve molluscs harvested in Sardinia, Italy - A.G. Mudadu; C. Spanu; S. Salza; G. Piras; M.T. Uda; L. Giagnoni; G. Fois; J.G. Pereira; J.C.F. Pantoja; S. Virgilio; T. Tedde (Food Research International, 2023)

Multinational evaluation of the BioFire® FilmArray® Pneumonia plus Panel as compared to standard of care testing - Christine C. Ginocchio; Carolina Garcia-Mondragon; Barbara Mauerhofer; Cory Rindlisbacher; L. Forcelledo; J. Fernández; R. Lienhard; H. Kerschner; G. M. Rossolini; L. Armand-Lefèvre; C. d’Humières; E. Cambau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
This study compared standard of care testing (SOC) to BioFire® FilmArray® Pneumonia plus Panel (PN plus ). PN plus detects 15 bacteria with semiquantitative log bin values, 7 antibiotic resistance markers, three atypical bacteria (AB), and eight viral classes directly from bronchoalveolar lavage-like specimens (BLS) and sputum-like specimens (SLS). Fifty-two laboratories from 13 European countries and Israel tested 1234 BLS and 1242 SLS with PN plus and SOC. Detection rates and number of pathogens/samples were compared for PN plus pathogens. PN plus bin values and SOC quantities were compared. Three thousand two hundred sixty-two bacteria in PN plus were detected by PN plus and/or SOC. SOC detected 57.1% compared to 95.8% for PN plus ( p ≤ 0.0001). PN plus semiquantitative bin values were less than SOC, equal to SOC, or greater than SOC in 5.1%, 25.4%, and 69.6% of results, respectively. PN plus bin values were on average ≥ 1 log than SOC values (58.5% 1–2 logs; 11.0% 3–4 logs). PN plus identified 98.2% of MRSA and SOC 55.6%. SOC detected 73/103 AB (70.9%) and 134/631 viruses (21.2%). PN plus detected 93/103 AB (90.3%) and 618/631 viruses (97.9%) ( p ≤ 0.0001). PN plus and SOC mean number of pathogens/samples were 1.99 and 1.44, respectively. All gram-negative resistance markers were detected. PN plus and SOC results were fully or partially concordant for 49.1% and 26.4% of specimens, respectively. PN plus was highly sensitive and detected more potential pneumonia pathogens than SOC. Semiquantification may assist in understanding pathogen significance. As PN plus generates results in approximately 1 h, PN plus has potential to direct antimicrobial therapy in near real time and improve antimicrobial stewardship and patient outcomes.

The GenTree Leaf Collection: Inter‐ and intraspecific leaf variation in seven forest tree species in Europe - Raquel Benavides; Bárbara Carvalho; Cristina C. Bastias; David López‐Quiroga; Antonio Mas; Stephen Cavers; Alan Gray; Audrey Albet; Ricardo Alía; Olivier Ambrosio; Filippos Aravanopoulos; Francisco Auñón; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait variation within species can reveal plastic and/or genetic responses to environmental gradients, and may indicate where local adaptation has occurred. Here, we present a dataset of rangewide variation in leaf traits from seven of the most ecologically and economically important tree species in Europe. Sample collection and trait assessment are embedded in the GenTree project (EU‐Horizon 2020), which aims at characterizing the genetic and phenotypic variability of forest tree species to optimize the management and sustainable use of forest genetic resources. Our dataset captures substantial intra‐ and interspecific leaf phenotypic variability, and provides valuable information for studying the relationship between ecosystem functioning and trait variability of individuals, and the response and resilience of species to environmental changes. Main types of variable contained We chose morphological and chemical characters linked to trade‐offs between acquisition and conservation of resources and water use, namely specific leaf area, leaf size, carbon and nitrogen content and their ratio, and the isotopic signature of stable isotope 13 C and 15 N in leaves. Spatial location and grain We surveyed between 18 and 22 populations per species, 141 in total, across Europe. Time period Leaf sampling took place between 2016 and 2017. Major taxa and level of measurement We sampled at least 25 individuals in each population, 3,569 trees in total, and measured traits in 35,755 leaves from seven European tree species, i.e. the conifers Picea abies , Pinus pinaster and Pinus sylvestris , and the broadleaves Betula pendula , Fagus sylvatica , Populus nigra and Quercus petraea . Software format The data files are in ASCII text, tab delimited, not compressed.

A 72-h intervention for improvement of the rate of optimal antibiotic therapy in patients with bloodstream infections - R. Murri; F. Taccari; T. Spanu; T. D’Inzeo; I. Mastrorosa; F. Giovannenze; G. Scoppettuolo; G. Ventura; C. Palazzolo; M. Camici; S. Lardo; B. Fiori; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Development and Characterization of Three Highly Informative EST-SSR Multiplexes for Pinus halepensis mill. and their Transferability to Other Mediterranean Pines - C. Leonarduzzi; I. Spanu; M. Labriola; S. C. González-Martínez; A. Piotti; G. G. Vendramin (Plant Molecular Biology Reporter, 2016)

Antibiotic resistance assessment in S. aureus strains isolated from raw sheep’s milk cheese - V. Spanu; S. Virdis; C. Scarano; F. Cossu; E. P. L. De Santis; A. M. Cosseddu (Veterinary Research Communications, 2010)